Proyecto de factibilidad para la implementación de una Escuela de fútbol en la Ciudad de Gonzanamá - Provincia de Loja - Veintimilla Castillo, Carlos Damián (2024)
The research consisted of carrying out a feasibility project in order to implement a soccer school in the city of Gonzanamá - province of Loja, based on market, technical and financial studies. The methodology used is enclosed in a quantitative, descriptive approach, supported by the deductive method. In addition, direct observation and a survey were the techniques used, along with instruments such as an observation guide and a questionnaire, which was directed to families with children from 5 to 15 years of age. The market study determined that the real demand is 236 children, obtaining an unsatisfied demand of 212 children; the installed capacity is 1440 students per year and the usage capacity will be 120 children. Within the legal and administrative study, it was determined that the school is formed as a simplified joint stock company (SAS), and its corporate name is Club Formativo "Inter Gonzanamá". In the financial study, an initial investment of $7,996.97 was established, 62% of the investment is own and the remaining 38% will be obtained through a bank loan. In the first year, $40,200.00 will be obtained with a profit of 25%, a registration cost of $35 dollars and a monthly payment of $25 dollars; Finally, the financial evaluation showed that the net present value (NPV) is $10,375.45, an internal return rate (IRR) of 53.76% and the benefit cost ratio (BCR) of $0. 23 cents of a dollar for each dollar invested, with a capital recovery period (PRC) of 1 year, 7 months and 6 days, the sensitivity analysis (SA) is 12.12% and a reduction of 8.13%. Given this background, it can be concluded that the project is viable.